Significance of Diapycnal Mixing Within the Atlantic Meridional Overturning Circulation - Cimoli, Laura; Mashayek, Ali; Johnson, Helen L.; Marshall, David P.; Naveira Garabato, Alberto C.; Whalen, Caitlin B.; Vic, Clement; De Lavergne, Casimir; Alford, Matthew H.; Mackinnon, Jennifer A.; Talley, Lynne D. (AGU Advances, 2023)
Diapycnal mixing shapes the distribution of climatically important tracers, such as heat and carbon, as these are carried by dense water masses in the ocean interior. Here, we analyze a suite of observation-based estimates of diapycnal mixing to assess its role within the Atlantic Meridional Overturning Circulation (AMOC). The rate of water mass transformation in the Atlantic Ocean's interior shows that there is a robust buoyancy increase in the North Atlantic Deep Water (NADW, neutral density γn ≃ 27.6–28.15), with a diapycnal circulation of 0.5–8 Sv between 48°N and 32°S in the Atlantic Ocean. Moreover, tracers within the southward-flowing NADW may undergo a substantial diapycnal transfer, equivalent to a vertical displacement of hundreds of meters in the vertical. This result, confirmed with a zonally averaged numerical model of the AMOC, indicates that mixing can alter where tracers upwell in the Southern Ocean, ultimately affecting their global pathways and ventilation timescales. These results point to the need for a realistic mixing representation in climate models in order to understand and credibly project the ongoing climate change. Key Points The cross-density mixing of water and tracers is quantified from observation-based estimates and numerical simulations in the Atlantic Ocean A net 0.5–8 Sv of North Atlantic Deep Water upwells diapycnally in the Atlantic Ocean (48°N–32°S), comprised of larger regional up/downwelling fluxes Tracer mixing in the deep Atlantic Ocean can significantly modify pathways and ventilation rates of tracers upwelling in the Southern Ocean Plain Language Summary The Atlantic Ocean meridional overturning circulation plays a key role in regulating the global heat and carbon budgets by inter-hemispheric transport of anthropogenic and natural tracers as well as water masses. While most of this transport occurs along nearly horizontal density surfaces in the ocean interior, vertical transport across density levels is key to bringing deep waters back to the surface. Such ...